ANALISIS PENGARUH BAHASA GAUL DI KALANGAN SISWA SD KELAS RENDAH TERHADAP PENGGUNAAN BAHASA INDONESIA - Nur Wahyuni (Program Studi Pendidikan Guru Pendidikan Anak Usia Dini (PGPAUD), 2022)
The rapid development of the flow of technology and media has had an impact on various sectors in society, one of which is the use of good and correct language. Nowadays, especially among elementary school students, a new trend is emerging, namely slang. Slang is a language that students usually use by using cool terms in everyday speaking. Some examples of slang vocabulary are